RETRACTED: Computer modelling as a basis for forestry and wood processing equipment design - Zyryanov M.A.; Petrova I.A.; Akhmatshin F.G.; Kotybayev E.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001